A conductivity study of preferential solvation of lithium ion in acetonitrile-dimethyl sulfoxide mixtures - Mozhzhukhina, Nataliia (2014)
The electrical mobility of LiPF6 in acetonitrile–dimethyl sulfoxide (ACN–DMSO) mixtures, a potential electrolyte in oxygen cathodes of lithium-air batteries, has been studied using a very precise conductance technique, which allowed the determination of the infinite dilution molar conductivity and association constant of the salt in the whole composition range. In the search for preferential Li+ ion solvation, we also measured the electrical conductivity of tetrabutylammonium hexafluorophosphate (TBAPF6), a salt formed by a bulky cation, over the same composition range. The results show a qualitative change in the curvature of the LiPF6 molar conductivity composition dependence for ACN molar fraction (xACN) ∼ 0.95, which was not observed for TBAPF6. The dependence of the measured Li/Li+ couple potential with solvent composition also showed a pronounced change around the same composition. We suggest that these observations can be explained by Li+ ion preferential solvation by DMSO in ACN–DMSO mixtures with very low molar fractions of DMSO.